Leksēmas ēna un pakrēslis latviešu izloksnēs - Stafecka, Anna (Baltistica, 1997)
LEXEMES ēna AND pakrēslis IN LATVIAN DIALECTSThe article deals with the analysis of the nomination of shadow in Latvian dialects.Standard Latvian ēna has two main meanings: „shadow of a tree” and „shadow of a living being”. The second meaning is more widespread in dialects than the first one and is connected semantically with dialectal ēns, ēna „ghost”.Some more archaic nominations of the shadow of a living being as sejs and susētuvis have been preserved in High Latvian.Lexeme pakrēslis in Standard Latvian has a meaning „shadow of the tree”, nevertheless in dialects it has also the meaning „shadow of a living being”.The examined dialectal material shows some archaic nominations of shadow of a living being while the change of meanings is observed in Standard Latvian.
Keywords: latvian; dialectology; lexicon; ēna; pakrēslis